PERANCANGAN APLIKASI MULTIMEDIA INTERAKTIF SEBAGAI MEDIA PEMBELAJARAN PENGENALAN HEWAN PADA TK ISLAM BAKTI 113 KOTO SALAK - Andikos, Adi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Sakinah Dharmasraya, 2019)
Computer Media Utilization Learning as one of the tools in the process of teaching learning which can be an arternative for teachers when delivering learning. In the process of learning to teach Islamic TK Bakti 113 still use a manual system with conventional media or print media in the form of pictures and writings in the book or on the board, especially the introduction of the animal world. Thus the author is interested to make a world teaching device of reptile-based animals using Macromedia Flash 8 Professional in early childhood. The results of this research is able to help and facilitate the pupil Islamic KINDERGARTEN 113 in learning about learning the introduction of reptile in multimedia animals.